If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8 + x)(8 + x) = 0 Multiply (8 + x) * (8 + x) (8(8 + x) + x(8 + x)) = 0 ((8 * 8 + x * 8) + x(8 + x)) = 0 ((64 + 8x) + x(8 + x)) = 0 (64 + 8x + (8 * x + x * x)) = 0 (64 + 8x + (8x + x2)) = 0 Combine like terms: 8x + 8x = 16x (64 + 16x + x2) = 0 Solving 64 + 16x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (8 + x)(8 + x) = 0Subproblem 1
Set the factor '(8 + x)' equal to zero and attempt to solve: Simplifying 8 + x = 0 Solving 8 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + x = 0 + -8 x = 0 + -8 Combine like terms: 0 + -8 = -8 x = -8 Simplifying x = -8Subproblem 2
Set the factor '(8 + x)' equal to zero and attempt to solve: Simplifying 8 + x = 0 Solving 8 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + x = 0 + -8 x = 0 + -8 Combine like terms: 0 + -8 = -8 x = -8 Simplifying x = -8Solution
x = {-8, -8}
| 5(4x+7)=120 | | 2(x+2)+6x=2-5x | | 5y-2(y+12)=27 | | 5x-3+6x-1=5-2(x+1) | | -(-2x+2)=14 | | 0.02(2t-4)=0.04(t-1)-0.04 | | 2(c+5)+5(3c-2)= | | 4(4r+6)=8-3(-5r-4) | | 5+2*(x-35)=(5+2)*x-35 | | 2x^2+28x+98=512 | | -55=4x+3x+1 | | 4+2y+7+6y=-13 | | 10x=20-15x | | y^2+y+22=0 | | -43+s=9 | | 10=9x+9 | | 6(3n+2)=9(9n+4)+1 | | 4x+0=8x+4 | | -33-3x=-6-2(1+4x) | | 0=sin^2(x)+cos(x)-0.5 | | -(9x-4y+7z)= | | 4(2d-3)-3d=3d-4 | | 3-(-12x+5)=x | | 0.5x-3.8=0.7 | | (3x+xy-2)-(2xy+x-4)= | | m=6+n | | [4(6-2)-5]-[7-(8-5)]= | | 15y^2+25y^3= | | 2a-6=6a-22 | | 600=(nsquared-n) | | 4h-13=7 | | -[10z-(19z+6)]=6+(8z+4) |